STUDY ON IN VITRO PROPAGATION AND DEVELOPMENT GROWTH OF GYNOSTEMMA PUBESCENS IN THE GREENHOUSE CONDITION - Nguyễn Thị Thanh Hằng; Lê Ái Vân; Đinh Văn Khiêm; Hoàng Văn Cương; Nguyễn Thị Phượng Hoàng; Phan Xuân Huyên (Tạp chí Khoa học Đại học Đà Lạt)
The Gynostemma pubescens plant, which is distributed mainly over the northern provinces, is a valuable and beneficial herb for human health. In this study, we investigated in vitro propagation and cultivation to evaluate the growth and development of Gynostemma pubescens in greenhouse conditions at Dalat city, Lamdong province. The results showed that MS medium supplemented with 1mg/l BA, 30 g/l sucrose, 8g/l agar, pH 5.8 was the best medium for shoot regeneration in vitro, with a shoot height of 1.84cm, and 10.50 shoots/explant. The MS medium contained 0.5mg/l TDZ, 30g/l sucrose, 8g/l agar, pH 5.8 was the most suitable medium for shoot regeneration in vitro, with a shoot height of 1.99cm, and 13.80 shoots/explant. Concentrations of IBA from 0 to 1 mg/l were appropriate for in vitro root regeneration, yielding a root regeneration rate of 100%. Coconut fiber powder was the most suitable substrate to transfer the plantlets to the greenhouse, with a survival rate of 100%, plant height of 9.73cm, and root length of 6.45cm. Humus proved the best substrate for plant development and growth, with a survival rate of 100%, plant height of 82.08cm, root length of 36.57cm and a fresh weight of 57.32g/plant. Watering with 100 ml of Nitrophoska fertilizer (2g/l) once a week was the best for plant growth, with a survival rate of 100%, height of 94.22cm, root length of 37.71cm, and a fresh weight of 59.38g/plant.